Dampak Penggunaan Email dan Instant Messenger terhadap Komunikasi Organisasi - Isabella Astrid Siahaya (Jurnal InterAct, 2014)
This article aims to know the impact of communication technology in organizational communication. As we know organizational communication has limitations because of distortions, one of which is caused by physical distance. However, with the development of technology, physical distance can be overcome by sending the work instruction, discussion, and decision-making through email or instant messengers like WhatsApp, Blackberry Messenger that can be accessed by simply using the phone. The advantage of instant messaging services is that it can be used by anyone, anywhere and anytime without the need to meet at the office. Technology changes offices into virtual ones. Distortion due to the dissolution of the message on one level in the organizational structure can be minimized because employees who are members within the group instant messenger can read messages simultaneously. Additionally, nonverbal message during face to face communication can be replaced with emoticons. But the downside is the time to work is often used for informal messaging not relevant with work and the employee ultimately can be drowned in a flood of data, including ones not needed to complete the job.